(untitled) (Applied Biological Research, 2023)
A field experiment was conducted for two years (2017-2019) at the College Farm, AICRP on Integrated Farming Systems unit, PJTSAU, Hyderabad (India) to identify the profitable cropping system module for different integrated farming systems under irrigated situation in sandy loam soils of Southern Telangana zone, Telangana (India). Among the ten cropping systems evaluated, sweet corn-vegetable (tomato) system was found more remunerative with B:C ratio 3.54, followed by okra-marigold-beetroot system with B:C ratio of 2.92. Among the ecological cropping systems for improving the soil health, Bt cotton + green gram (1:3)-groundnut cropping system gave significantly higher rice grain equivalent yield (13,687 kg ha-1), however the net returns were high (₹ 1,37,259 ha-1) in pigeon pea + green gram (1:7)-sesame cropping system. Out of the two systems tested to meet the household nutritional security, pigeon pea + maize (1:3)-groundnut system gave higher rice grain equivalent yield (13,772 kg ha-1) with higher net returns (₹ 1,35,959 ha-1). Within the two fodder crops/cropping systems, fodder maize-lucerne system showed higher B:C ratio (1.64). Fodder systems were more exhaustive than all other cropping systems. However, within two years of experimentation the changes in physicochemical properties and soil fertility status were not significantly affected.